PAN4AJ: A Programming AssistaNt for Introductory AspectJ Programming (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Teaching and learning Aspect-Oriented Programming (AOP) usually involves learning a programming language with a large amount of complexity. Beginners very often spend more time dealing with syntactical complexity than learning the underlying principles of aspect-orientation or solving the problem. Additionally, the textual nature of most programming environments works against the learning style of the majority of beginners. Consequently, a support tool for teaching and learning AOP is, therefore, desirable.This paper offers a preview of the first stage of our research project, in which we aim to introduce a new way for the Aspect-Oriented Programming (AOP) paradigm. We intend to provide an easy-to-use educational tool for both teachers and beginners. We propose PAN4AJ – a Programming AssistaNt for AspectJ language, the most widely used AO-based implementation. The language together with the tool are an attempt to integrate visual paradigm techniques with the text-based method to support programming activities.